Equitable distribution of low-cost houses : a Malaysian legal perspective - Sufian, Azlinor (2009)
It has been stated in the Ninth Malaysia Plan that continuous efforts shall be undertaken to ensure all Malaysians of all income levels shall have access to adequate, affordable and quality housing with greater emphasis on the lower income group with better urban services and healthy living. The Ninth Malaysia Plan also emphasised that the private sector shall be encouraged to build more low-cost and low-medium-cost houses in their mixed-development projects while the public sector shall concentrate on building low-cost houses as well as houses for public sector employees. It is therefore sufficiently clear that the government has been employing serious strategies in achieving this aim. Despite the active involvement of both public and private sectors in providing low-cost houses to the lower income group however there are a few drawbacks in implementing the objectives of the Ninth Malaysia Plan. For instance the issue of improper distribution of low-cost houses has always been brought up by certain quarters in society. This paper will delve into the Open Registration System ("ORS") introduces by the Ministry of Housing and Local Government of Malaysia ("MHLG") in managing the registration of intended purchasers of low-cost houses and distributing it to the targetted groups. This paper will try to identify the drawbacks of the system and suggest reforms in terms of legal and institutional frameworks.